2020
DOI: 10.3390/pr8080998
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization for Green Synthesis of Silver Nanoparticles Using Indonesian Medicinal Plant Extracts

Abstract: Silver nanoparticles (AgNPs) are an interesting metal nanoparticle that can be incorporated into pharmaceutical products, including for diabetic foot ulcers as an antimicrobial agent. Green synthesis of AgNPs using plant extracts has been drawing much attention as it is simple, eco-friendly, stable, and cost-effective. This present study was performed to evaluate the potential of three Indonesian medicinal plant extracts, namely Phyllanthus niruri (PN), Orthosiphon stamineus (OS), and Curcuma longa (CL), as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
4
8
0
Order By: Relevance
“…It is also noticed that the PDI results were around 0.5, which is moderate polydispersity for the prepared nanoparticles from all of the extracts. Although the PDI value was relatively high, a higher PDI value of biosynthesized AgNPs was reported by Kartini et al, who stated that PDI > 0.7 is considered polydisperse [28]. Similar values were obtained by Khan et al and Shahzad et al [29,30].…”
Section: Characterization Of Silver Nanoparticles Formulaesupporting
confidence: 73%
“…It is also noticed that the PDI results were around 0.5, which is moderate polydispersity for the prepared nanoparticles from all of the extracts. Although the PDI value was relatively high, a higher PDI value of biosynthesized AgNPs was reported by Kartini et al, who stated that PDI > 0.7 is considered polydisperse [28]. Similar values were obtained by Khan et al and Shahzad et al [29,30].…”
Section: Characterization Of Silver Nanoparticles Formulaesupporting
confidence: 73%
“…Therefore, the determined magnitude of zeta potential, −49.5 mV (Figure 10b), with an overall negative charge on the surface of synthesized AgNPs, roughly predicted the stability of LTEO-AgNPs, which is supported by the existing literature reports [36]. Stability is one of the parameters that ensures the life span of AgNPs can be used effectively in different application areas [33,37,56]. The physicochemical stability of LTEO-AgNPs was studied over 6 months using UV-Vis spectra analysis.…”
Section: Characterization Of Lteo-agnpssupporting
confidence: 72%
“…The demonstrated FT-IR spectra of LTEO were more probably for major functional groups of oxygenated compounds and aromatic compounds. Moreover, the functional groups of chemical constituents of LTEO are supported by the existing literature review [33,39] and the structures of chemical compounds identified by GC/MS analysis in this study.…”
Section: Instrumental Analyses Of Lteosupporting
confidence: 71%
See 2 more Smart Citations